Human Flourishing and Adult Education - Davin J. Carr-Chellman; Michael Kroth; Carol Rogers-Shaw (Adult Education Research Conference, 2022)
Human flourishing, a goal of adult education, is grounded in a capabilities approach and focuses on community and justice based endeavors that generate meaning and contribute to well-being.
Keywords: human flourishing; capabilities; relationship building